Depression and Type 2 Diabetes: Dissecting the Causal Mechanisms - Awani Kumar Diwakar (Sumatera Medical Journal, 2024)
Background: Depression and Type 2 Diabetes (T2D) are two prevalent and debilitating chronic conditions that often coexist and exhibit a bidirectional relationship. Objective: This aims was to dissect the causal mechanisms underlying the association between depression and T2D, shedding light on the complex interplay between these two disorders. Methods: This was review paper that will explore about epidemiological evidence that found association between depression and an increased risk of developing T2D, as well as a reciprocal relationship where T2D serves as a risk factor for depression onset. Results: Various biological, psychological, and behavioral mechanisms have been proposed to underlie this bidirectional relationship. Depression is thought to contribute to the development of T2D through dysregulation of neuroendocrine pathways, increased inflammation, alterations in lifestyle behaviors, and poor treatment adherence. Conversely, T2D may exacerbate or precipitate depression through mechanisms involving insulin resistance, hyperglycemia-induced neuronal damage, inflammation, and the impact of chronic illness on psychological well-being. Conclusion: Understanding the causal mechanisms underlying the depression-T2D relationship is crucial for informing clinical practice, public health strategies, and the development of personalized interventions aimed at mitigating the burden of these interconnected disorders.